Real Time Image Processing on a Portable Aid Device for Low Vision Patients - Ros, E.; Díaz, J.; Mota, S.; Vargas-Martín, F.; Peláez-Coca, M. D. (Reconfigurable Computing: Architectures and Applications, 2006)
Low vision patients are subjects with very restricted visual fields or low contrast. There are different pathologies affecting this kind of patients. From a functional point of view the residual vision can be classified in three categories: low contrast vision, tunnel vision and peripheral vision. This contribution describes simple real-time image processing schemes that can help this kind of patients. The presented approaches have been implemented in specific hardware (FPGA device) to achieve real-time processing with low cost portable systems. This represents a very valid alternative to optical aids that are widely used in this field.